Genotype-phenotype correlation of deletions and duplications of 4p: case reports and literature review - Zhang, Xuan; Lu, Hongjuan; Yang, Hanran; Ji, Yichen; Liu, Huixin; Liu, Wenjian; Li, Jiayi; Yang, Zhixian; Sun, Wei (Frontiers in Genetics, 2023)
Structural rearrangements of chromosome 4p gives rise to a group of rare genomic disorders that mainly result in two different clinical entities: Wolf-Hirschhorn syndrome (WHS) and partial 4p trisomy. The severity of the phenotype depends on the size of the deletion or locus duplication. Here, we present two unrelated individuals with a copy number variation of chromosome 4p. Inverted duplication deletions (inv dup-del) in 4p are particularly rare. Case 1 describes a 15-year-old girl with a 1.055 Mb deletion of terminal 4p, distal to the recognized critical region of WHS, and a large duplication of 9.6 Mb in size from 4p16.3 to p16.1. She had postnatal development delay, mental retardation (especially pronounced in speech), seizure/electroencephalogram anomalies, and facial dysmorphic features. This unusual chromosomal imbalance resulted in the WHS phenotype rather than the 4p trisomy syndrome phenotype. Case 2 describes a 21-month-old boy with a 1.386 Mb terminal 4p deletion who presented with slight developmental delay, borderline intellectual disability, and seizures. Our observations suggest that terminal chromosome 4p deletion is more pathogenic than the concomitant partial 4p duplication, and some regions of the 4p terminal may have regulatory effects on the remaining region of 4p. About nine cases have been reported thus far to date, and our study delineates further genotype-phenotype correlations about terminal 4p duplication-deletions for predicting disease prognosis and patient counseling.